Pengaruh Brand Image dan Product Quality Terhadap Customer Loyalty yang Dimediasi Customer Satisfaction pada Pakaian Muslim - Haura Az Zahra; Feryyal Abadi (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The development of the Muslim fashion industry in Indonesia is increasingly important, as the majority of the population is Muslim and the awareness of wearing fashionable sharia clothes increases. This increase in demand encourages business actors like Elzatta to maintain product quality and brand image to increase customer satisfaction and loyalty. This study aims to examine the influence of brand image and product quality on customer satisfaction, as well as its impact on customer loyalty on Elzatta consumers in Jakarta. The study used a quantitative approach with SEM-PLS. Data was collected from 110 respondents through an online questionnaire. The results show that brand image and product quality have a positive effect on customer satisfaction. Furthermore, customer satisfaction is a mediating variable in the relationship between these two variables to customer loyalty. However, brand image does not have a direct effect on loyalty because consumer expectations are not met. The R² value of 0.63 for customer loyalty and 0.623 for customer satisfaction indicates that the model belongs to the moderate category. An SRMR value of 0.085 indicates a fairly decent model, although an NFI of 0.716 indicates that the model is fit. This research provides important implications for Elzatta's management to continue to maintain quality, innovation, and service to strengthen customer loyalty.